Tabu-Games in Improving the German Vocabulary - Najwa Almaida; Abdul Kasim Achmad; Femmy Angreany (Universitas Negeri Makassar, 2026)
Abstract. This study aims to determine the planning, describe the implementation, and analyze the result of applying Tabu-Games media to improve German vocabulary among Grade XII.9 students at MAN 1 Kota Makassar. This research is a Classroom Action Research (CAR) consisting of two cycles. The research subject were 32 student of class XII.9 at MAN 1 Kota Makassar and one German language teacher. The data consist of qualitativ and quantitativ types. Qualitativ data were obtained through teacher and student observations, while quantitative data gathered through German vocabulary test in Cycle I and Cycle II. The result of the vocabulary tests showed an average score of 71,46% in Cycle I, which increaseed to 86,46% in Cycle II. These findings indicate that the application of Tabu-Games media effectively improves the German vocabulary of Grade XII.9 student at MAN 1 Kota MakassarKeyword: German Vocabulary, Tabu-Games Media, Vocabulary Improvement, Classroom Action Research